Vpliv Slovenskega državnega holdinga na korporacijsko upravljanje v Sloveniji - Bratina, Borut (Podjetje in delo, 2014)
The author presents novelties in corporate governance of the state-owned enterprises in Slovenia according to new Slovenian Sovereign Holding Act. The article is focused on the presentation of the OECD Guidelines on Corporate Governance of State-Owned Enterprises and on the consideration of these guidelines in Slovenian legislation and comparison between Slovenian Sovereing Holding (SSH) and former Agency for State's Capital Investments (ASCI).
Keywords: gospodarske družbe; gospodarsko pravo; korporacije; management; upravljanje; vodenje